2010
DOI: 10.1007/s00436-010-2153-y
|View full text |Cite
|
Sign up to set email alerts
|

Identification of astigmatid mites using ITS2 and COI regions

Abstract: Identification of astigmatid mites based on their morphological characteristics is difficult because of the similarity of their organs, especially in immature mites. The ribosomal second internal transcribed spacer (ITS2) and the mitochondrial cytochrome oxidase subunit I (COI) regions are highly conserved in the eukaryotes and are usually used as barcodes. The ITS2 and COI regions of six species of astigmatid mites (Aleuroglyphus ovatus, Blomia tropicalis, Dermatophagoides farinae, Dermatophagoides pteronyssi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
35
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(37 citation statements)
references
References 30 publications
2
35
0
Order By: Relevance
“…The results were consistent with studies reported by Noge et al (2005), in which a slightly higher intraspecific variation among the ITS2 sequences of A. ovatus was observed as compared to other astigmatid mites. Another reason was probably due to the ITS2 region of A. ovatus that was not homogenized completely within and/ or between individuals as been observed by Yang et al (2011).…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…The results were consistent with studies reported by Noge et al (2005), in which a slightly higher intraspecific variation among the ITS2 sequences of A. ovatus was observed as compared to other astigmatid mites. Another reason was probably due to the ITS2 region of A. ovatus that was not homogenized completely within and/ or between individuals as been observed by Yang et al (2011).…”
Section: Discussionmentioning
confidence: 95%
“…Species identification in mite cultures is a key factor in standardization of allergen production especially when the colonies established are from field-derived mites (Beroiz et al, 2014). Proper species identification may contribute to improved management of mite associated allergies as they produce species-specific allergens besides being an essential first step of acarological evidence for a legal investigation (de Pancorbo et al, 2004;Yang et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Although rDNA ITS2 and 630-bp mtDNA COI at the 5′ terminal have been used for intra-and interspecies classification and identification in Acari (Zhao et al 2014;Yang et al 2011;Chitimia et al 2009), it is unclear whether the two genes are suitable for intergeneric identification. In the present study, it was confirmed for the first time that rDNA ITS2 can be used not only for intra-and interspecies identification (intraspecific divergences threshold≤5.20 %, interspecific divergences threshold≥6.18 %) but also for interspecies and intergenera identification (interspecific divergences threshold≤14.86 %, intergeneric divergences threshold≥ 15.72 %) with an obvious barcoding gap.…”
Section: Discussionmentioning
confidence: 99%
“…Since mitochondrial cox1 gene was proposed as a DNA barcode for animal species identification by Hebert et al in 2003, it has been widely and effectively used in the classification, identification, and phylogenetic analysis of thousands of species (Hebert et al 2003a;Costa et al 2007;Yang et al 2011;Lv et al 2014). However, as far as we have been concerned, there have been no reports on DNA barcode for Demodex.…”
Section: Introductionmentioning
confidence: 96%